Members of the Interwar Academic Union All-Polish Youth at the University of Poznań. Outline of the Problem - Kimel, Klaudia (Sensus Historiae, 2023)
The article discusses both the presence and activities of women in the interwar “All-Polish Youth” Academic Union. Its main goal is to emphasize the participation of female students in the mentioned organization, despite the lack of previous interest of researchers in this topic, and to try to indicate the main areas of their activity. It is important to point out the lack of extensive sources, which complicates the research. Despite this, the discovered names of female students and information about their activities suggest their significant contribution to the organization as well as their commitment to the ideology of the academic union.